Controlled 3D patterns formed via FDM printing atop pre-stretched textile - Tee, Ying Hong (Nanyang Technological University, 2024)
Using patterns printed onto pre-stretched textiles, the contraction of the textile to its original size is disrupted and controlled 3D deformation occurs.